Triple Water Vapour–Isotopologues Record from Chhota Shigri, Western Himalaya, India: A Unified Interpretation based on δ17O, δ18O, δD and Comparison to Meteorological Parameters - Ranjan, S.; Ramanathan, AL.; Keesari, Tirumalesh; Singh, Virendra B.; Kumar, Naveen; Pandey, Manish; Leuenberger, Markus C. (Frontiers in Earth Science, 2021)
The objective of this study is to investigate and understand the source and transportation of water vapour in the western Himalayan region – that is still missing – using water vapour stable isotopologues and air mass trajectory diagnostics. We report the first-time triple oxygen isotopic compositions of water vapour from high altitude western Himalaya (Chhota Shigri, India) and compare them with meteorological conditions at the site of investigation as well as tracked backwards through the Lagrangian air mass trajectory diagnostics. A total of 21 water vapour samples were collected using a quantitative cryogenic method. d17O and d18O show a significant correlation coefficient of 0.999 (p <0.01). The temporal variations of d17O, d18O, dD, D-excess and 17O-excess are 1.2 ‰, 2.3 ‰, 17.3 ‰, 11.6 ‰ and 39.5 permeg, respectively. d17O and d18O exhibits significant (p<0.05) diurnal variations along with meteorological parameters. Chhota Shigri vapour isotopic results show a clear difference in the 17O-excess value compared to near the south Indian Ocean and the Southern Ocean regions, reflecting the influence of local moisture recycling at the continental site. NCEP/NCAR reanalyses show lower SH during the sampling period (September, ending month of the summer monsoon) favouring evaporative conditions which are further corroborated through the Lagrangian moisture diagnostics suggesting frequent moisture uptake and moisture loss in specific regions.